Dangerous Fishes of the Eastern and Southern Arabian Peninsula - Jawad, Laith A. (Springer International Publishing, 2018)
This book is devoted to the dangerous fishes found offshore the eastern and southern Arabian Peninsula. It covers information about the main groups of dangerous fish species i.e., biting and predator fish group, venomous stinging fish, electric shock fish, harmful stinging fish, and poisonous fish. In the latter group, the book gives details about fishes that cause several types of toxicities to human. The purpose of this book is to thoroughly introduce life, nature and methods of dangerous fishes in order to form awareness about their danger and to take the proper preventive steps. It will appeal to researchers, scholars, divers, the sea coast visitors and students of marine biology as it is highly informative and carefully presented. This book is the first of its kind for the Arabian region in particular and the Middle East in general.